2021
DOI: 10.1002/glia.24110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of monoamine oxidase B prevents reactive astrogliosis and scar formation in stab wound injury model

Abstract: Reactive astrocytes manifest molecular, structural, and functional alterations under various pathological conditions. We have previously demonstrated that the reactive astrocytes of the stab wound injury model (STAB) display aberrant cellular gamma‐aminobutyric acid (GABA) content and tonic GABA release, whereas the active astrocytes under enriched environment (EE) express high levels of proBDNF. However, the role of monoamine oxidase B (MAO‐B) in reactive astrogliosis and hypertrophy still remains unknown. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Astrocytes release numerous neuroactive molecules, including the classical inhibitory neurotransmitter GABA ( Garcia-Caceres et al, 2019 ; Lee et al, 2010 ; Yoon and Lee, 2014 ). Accumulating evidence suggest that elevated levels of GABA in reactive astrocytes act as a common molecular mechanism in various neuroinflammatory diseases ( Chun and Lee, 2018 ), such as Alzheimer’s disease ( Chun et al, 2020 ; Jo et al, 2014 ), Parkinson’s disease ( Heo et al, 2020 ), recovery after stroke ( Nam et al, 2020 ), stab-wound injury ( Chun et al, 2022 ), epileptic seizure ( Pandit et al, 2020 ) and inflammation-induced anxiety ( Shim et al, 2019 ). Consistently, it has been reported that extracellular GABA in mediobasal hypothalamus (ARC and VMH) is elevated in DIO mice ( Zhang et al, 2017 ).…”
Section: Consequences Of Reactive Astrocytesmentioning
confidence: 99%
“…Astrocytes release numerous neuroactive molecules, including the classical inhibitory neurotransmitter GABA ( Garcia-Caceres et al, 2019 ; Lee et al, 2010 ; Yoon and Lee, 2014 ). Accumulating evidence suggest that elevated levels of GABA in reactive astrocytes act as a common molecular mechanism in various neuroinflammatory diseases ( Chun and Lee, 2018 ), such as Alzheimer’s disease ( Chun et al, 2020 ; Jo et al, 2014 ), Parkinson’s disease ( Heo et al, 2020 ), recovery after stroke ( Nam et al, 2020 ), stab-wound injury ( Chun et al, 2022 ), epileptic seizure ( Pandit et al, 2020 ) and inflammation-induced anxiety ( Shim et al, 2019 ). Consistently, it has been reported that extracellular GABA in mediobasal hypothalamus (ARC and VMH) is elevated in DIO mice ( Zhang et al, 2017 ).…”
Section: Consequences Of Reactive Astrocytesmentioning
confidence: 99%
“…Our study sheds a light on the missing link between the reactive astrogliosis and obesity, delineating the molecular and cellular mechanisms of how MAOB-dependent production of GABA leads to inhibition of energy expenditure and facilitation of fat storage. Elevated activity of MAOB and elevated levels of MAOB-dependent GABA have been highly implicated in the reactive astrocytes that are found in various neuroinflammatory diseases such as Alzheimer’s disease, Parkinson’s disease, stab-wound injury model and et cetera (Chun et al, 2021; Jo et al ., 2014; Nam et al, 2021; Pandit et al, 2020; Shim et al, 2019). The growing list of reports all point to the common molecular mechanism of how resting astrocytes transform into reactive astrocytes via the putrescine-degradation pathway involving MAOB under the conditions of aversive stimulations such as toxin challenges and viral infections, which usually accompany neuroinflammation (Chun et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Monoamine oxidases (MAOs), including MAO-A and MAO-B, are enzymes that catalyze the oxidation of monoamines and are bound to the outer mitochondrial membrane in cells of several organs, such as the brain, liver, kidney, and the immune system 14,15 . Previous reports have suggested that MAO inhibitors can alleviate joint symptoms such as pain and stiffness in patients with RA, and there is growing evidence that MAO-B may be associated with systemic inflammation, especially neuroinflammation [16][17][18] . Moreover, joint inflammation in RA patients is associated with hydrogen peroxide (H 2 O 2 ) production, which might be mediated by MAO-B and mitigated by antioxidant administration, suggesting that MAO-B could be an effective therapeutic target for RA 17,19,20 .…”
Section: Introductionmentioning
confidence: 99%